2002
DOI: 10.1007/s00424-002-0813-1
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear pore ion channel activity in live syncytial nuclei

Abstract: Nuclear pore complexes (NPCs) are important nanochannels for the control of gene activity and expression. Most of our knowledge of NPC function has been derived from isolated nuclei and permeabilized cells in cell lysates/extracts. Since recent patch-clamp work has challenged the dogma that NPCs are freely permeable to small particles, a preparation of isolated living nuclei in their native liquid environment was sought and found: the syncytial nuclei in the water of the coconut Cocos nucifera. These nuclei ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, evidence has been presented for cytosolic-nuclear Ca 2ϩ gradients and other indications of independent regulation of nuclear Ca 2ϩ under specific conditions (9,11). It was pointed out that most of our knowledge of nuclear pore function has been derived from isolated nuclei and permeabilized cells in cell lysates/extracts, and that patch-clamp study of isolated living nuclei in their native liquid environment revealed no transport of physiological ions (10). Independent Ca 2ϩ regulatory mechanisms, if validated, would be consistent with the recently expressed concept of the nucleus as a ''cell within a cell'' (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence has been presented for cytosolic-nuclear Ca 2ϩ gradients and other indications of independent regulation of nuclear Ca 2ϩ under specific conditions (9,11). It was pointed out that most of our knowledge of nuclear pore function has been derived from isolated nuclei and permeabilized cells in cell lysates/extracts, and that patch-clamp study of isolated living nuclei in their native liquid environment revealed no transport of physiological ions (10). Independent Ca 2ϩ regulatory mechanisms, if validated, would be consistent with the recently expressed concept of the nucleus as a ''cell within a cell'' (24).…”
Section: Discussionmentioning
confidence: 99%
“…Some aspects of nuclear Ca 2ϩ , in particular its capacity for independent regulation, have been controversial because of the existence of nuclear pore complexes that appeared to allow free diffusion of Ca 2ϩ between cytosol and nucleoplasm (8). However, some studies have suggested the existence of cytoplasmnucleoplasm Ca 2ϩ gradients (9,10), and there is growing evidence for independent Ca 2ϩ regulation in that organelle (11). Adding to the story was the discovery of a mechanism for Ca 2ϩ flux between NE and nucleoplasm, mediated by sodium-calcium exchanger (NCX) activity in the inner membrane of the NE of neural-and certain other cells; analyses that revealed the latter exchanger included immunoprecipitation/immunoblotting (IP/IB), immunocytochemistry, RT-PCR, and 45 Ca 2ϩ uptake by the NE of isolated nuclei (12,13).…”
Section: R Egulation Of Nuclear Camentioning
confidence: 99%
“…54 Finally, several other studies using isolated nuclei from either cardiac myocytes or coconut syncitia demonstrated that plasmids could be imported through the NPC in a manner that was dependent on cytoplasmic and nuclear extracts, as well as the presence of the SV40 DTS. [55][56][57] Moreover, these studies also demonstrated that the isolated nuclei could not only import the DNA but also export expressed mRNA leading to reporter gene expression.…”
Section: Protein Factor Requirements For Dna Nuclear Importmentioning
confidence: 86%
“…A sizeable amount of syncytial nuclei is found in the voluminous liquid known as coconut water (hundreds of millilitres per coconut). NPCs from living, intact coconut syncytial nuclei also displayed the on-off switching typical of ion channel gating behavior (Bustamante 2002a). In addition, our studies showed that coconut water has the capacity to transcribe and translate artificial DNA vectors (e.g., pEGFP), thus facilitating studies of the dynamics of the translocation of macromolecules and (or) nanoparticles along NPCs (Bustamante 2002a).…”
Section: Brief Historymentioning
confidence: 96%
“…These nuclei are naked, (i.e., devoid of any other subcellular membrane) and are suspended in their own natural liquid environment, full of substrates for transcription, translation, replication, etc. Furthermore, syncytial nuclei occur in a large variety of preparations (some more amenable for nuclear electrophysiology studies) (Bustamante 2002a). A sizeable amount of syncytial nuclei is found in the voluminous liquid known as coconut water (hundreds of millilitres per coconut).…”
Section: Brief Historymentioning
confidence: 99%